2007
DOI: 10.1038/sj.tpj.6500438
|View full text |Cite
|
Sign up to set email alerts
|

Reduced folate carrier-1 80G>A polymorphism affects methotrexate treatment outcome in rheumatoid arthritis

Abstract: The folate antagonist methotrexate (MTX) is a drug currently used in the treatment of rheumatoid arthritis (RA). MTX enters the cells through the reduced folate carrier (RFC-1) and is activated to polyglutamates. Previous studies have shown that RFC-1 expression may influence the efficacy of therapy with MTX. The studies suggest that G80A polymorphism in RFC-1 is associated with altered folate/antifolate levels and the subjects carrying homozygous mutant 80AA genotype tend to have higher plasma folate and MTX … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
39
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 20 publications
2
39
1
2
Order By: Relevance
“…18,19 Studies of rheumatoid arthritis patients in MTX monotherapy have, like the functional study of MTX uptake by Baslund et al, 14 demonstrated better MTX efficacy in AA variants. 20,21 However, only 2 studies have previously investigated the effect on outcome in childhood ALL: Rocha et al 22 could not demonstrate any significant effect on cure rate in 246 children with ALL, whereas Laverdiere et al 11 in a study of 204 patients found a reduced relapse rate for patients with the G-allele. However, a different MTX treatment strategy was used in the latter study, and neither of the 2 studies explored the impact of chromosome 21 copy number.…”
Section: Introductionmentioning
confidence: 99%
“…18,19 Studies of rheumatoid arthritis patients in MTX monotherapy have, like the functional study of MTX uptake by Baslund et al, 14 demonstrated better MTX efficacy in AA variants. 20,21 However, only 2 studies have previously investigated the effect on outcome in childhood ALL: Rocha et al 22 could not demonstrate any significant effect on cure rate in 246 children with ALL, whereas Laverdiere et al 11 in a study of 204 patients found a reduced relapse rate for patients with the G-allele. However, a different MTX treatment strategy was used in the latter study, and neither of the 2 studies explored the impact of chromosome 21 copy number.…”
Section: Introductionmentioning
confidence: 99%
“…An example of the latter is G80A, which could affect plasma folate and MTX concentrations. 14 We hypothesized that, first, differences in the expression of folate enzymes (DHFR and RFC) in osteosarcoma tissues might be predictors of the response to MTX chemotherapy and thus, potentially, of survival; and second, that germline variations in folate pathway enzymes such as RFC, MTHFR, TYMS, SHMT, and MTR might affect the response to MTX chemotherapy or its toxicity. To test these hypotheses, we determined the genotype in 96 cases of pediatric osteosarcoma treated with HD-MTX and analyzed the level of expression of different enzymes involved in folate metabolism (Figure) in a subset (n = 34) of these patients for whom tumor tissues were available.…”
Section: Introductionmentioning
confidence: 99%
“…The therapeutic effect of L-MTX has been reported to be dependent on the SNP of hRFC in patients with rheumatoid arthritis or childhood acute lymphoblastic leukemia. 26,27) It has also been reported that the transport parameters of L-MTX were very similar in the H27-and R27-hRFCs when the transporters were expressed stably in K562 cells, although minor differences were observed in the K i values of other anti-folates. 22) In the current study, the K m of L-MTX in R27-hRFC-HEK293 cells was approximately 2-fold greater than it was in H27-hRFC-HEK293 cells, and the V max of L-MTX in R27-hRFC was approximately 20-fold greater than that in H27-hRFC (Fig.…”
Section: Discussionmentioning
confidence: 81%